Male Veteran Intimate Partner Violence (IPV) Program Outcomes. Issue 2 (3rd March 2016) - Schaffer, Bradley J.
Abstract : The prominence and incidence of intimate partner violence (IPV) with male military veterans vary, but generally there is consensus that screening and intervention does help reduce IPV. Intervention is generally provided in the community via Batterer Intervention Programs. However, at the Department of Veterans Affairs (VA) intervention is provided via the Domestic Relations Clinic. Nationally the VA has limited treatment for male IPV. An aggregate sample ( n = 178) of participants was assessed using the Domestic Violence/Abuse Screen to measure covariate pre-test and post-test outcomes, program failure, and recidivism. The treatment approach is psycho-educationally based to meet the challenging and unique needs of the military veteran population. The results contribute to a more comprehensive understanding of IPV and highlight the need for more intervention and prevention approaches.